Research on container for high-level radioactive waste vitrification product - Zhinan Yan; Wei Li; Kai Cui; Yinan Xie; Xue Zhang (International Journal of Advanced Nuclear Reactor Design and Technology, 2025)
Product containers for high-level radioactive waste liquid vitrified glass are critical components for ensuring continuous and stable operation of vitrification plants. Given the substantial demand for such containers in China, it is imperative to develop product containers with independent intellectual property rights. This article presented the comprehensive structural design, mechanical analysis and test verification of product containers, considering their usage processes and functional requirements within vitrification plants. The resulting containers exhibited excellent high-temperature resistance, remote-operations, stacking functionality and anti-drop performance, fully meeting the usability and safety demands of the product container in the vitrification plants.